KONTRIBUSI KEPEMIMPINAN TRANSFORMASIONAL TERHADAP PENINGKATAN KINERJA ORGANISASI - Umri, kamila; Sukriadi, Sukriadi (UNM (Universitas Negeri Makasar), 2024)
This research focuses on the contribution of transformational leadership, which is a leadership style that tries to inspire and motivate followers to achieve higher goals. This leadership style can partly help improve organizational performance. The purpose of this study is to determine and analyze the effect of transformational leadership on organizational performance. The method approach in this research is to use library research methods in which researchers read and study journals, books and literature related to variable factors and research indicators and then analyzed using content analysis methods, namely qualitative descriptive analysis. Based on the analysis that has been done, it can be taken that transformational leadership has a positive influence on the performance of the organization. The findings of this study are that transformational leaders are able to increase the motivation, commitment, and performance of their followers which ultimately affect the overall performance of the organization.